The Use of the Muroja'ah Method in Improving of Reading Al Qur'an - Saputra, Rijal; Suhono, Suhono; Irhamudin, Irhamudin; Wicaksono, Helmi (Bulletin of Pedagogical Research, 2023)
The article aimed to determine the use of the muroja'ah method in improving the students to read the Al Qur’an at Junior High School IT Hidayatu Muslimin and Eureka English Course. This study used a qualitative method. The sample was 30 students and collecting data used observation, interviews and documentation. While the analysis technique used triangulation. The results of showed that the use of muroja'ah which was applied to class VII students of SMP IT Hidayatu Muslimin and studentas of Eureka English Course used the muroja'ah method overcome children's difficulties in reading the Qur'an. Many changes have occurred, Al-Qur'an reading activities were also more effective and have been carried out properly. In the Al-Qur'an reading activity using the muroja'ah method there are still some children who still experience difficulties in reading the Al-Qur'an but the teacher continues to guide the child until he is fluent in reading the Al-Qur'an. Keywords: Muroja'ah Method, Improving Reading Al Qur’an, Reading Al Qur’an